The role of PI3K inhibitors in the treatment of malignant lymphomas. Issue 3 (23rd February 2021) - Berning, Philipp; Lenz, Georg
Abstract: Deregulated phosphatidylinositide 3-kinase (PI3K) signaling plays a crucial role in the biology of different lymphoma entities leading to the proliferation and survival of the malignant cells. Due to novel treatment options and modern supportive care, the outcome of patients with lymphomas has significantly improved in the past years. However, patients with relapsed or refractory disease still have a limited prognosis. PI3K inhibitors represent a modern and effective therapeutic option for patients with different types of lymphoma. However, the efficacy of PI3K inhibitors varies among lymphoma entities. Additionally, severe toxicity including infectious and autoimmune complications leading to therapy-related deaths has been observed. Next-generation PI3K inhibitors show promising efficacy and manageable toxicity profiles. Future research might identify effective combinatorial therapy approaches for PI3K inhibitors to further improve response rates. This review discusses the most recent developments in the field of PI3K inhibition in different subtypes of lymphoma.